Glencoe : Literature : (Glencoe/McGraw-Hill, 2002)
In this lively collection of classic and contemporary literature, you will find much to amuse, surprise, delight, engage, and inform you. A wide variety of selections-including poems, plays, short stories, essays, autobiographies, and news articles on a broad range of themes-offers you the chance to hear talented authors in all their diversity, as well as to experience and learn about the people, places, and ideas that moved them.